Upskilling and Reskilling Non-Communicable Disease Cadres for Increasing Chronic Disease Management - Lestari, Diana Tri; Retnowati, Eko; Aman, Syahrial (Jurnal Pengabdian Masyarakat, 2025)
Purpose: Non-communicable diseases (NCDs) are often chronic diseases, with the incidence rate increasing every year. All elements are involved in the prevention and management of NCDs. Likewise, NCDs posbindu cadres are the spearhead in the community. This community service aims to improve the knowledge and skills of NCDs posbindu cadres in efforts to prevent, early detect, manage and report NCDs. Method: The method used in community service uses a knowledge transfer approach, science and technology diffusion, asset-based community development and participatory action programs. All cadres of NCDs and Puskesmas were involved in this activity. The program implementation procedure is preceded by socialization, implementation, monitoring and evaluation. Practical Application: The implementation of upskilling and reskilling cadre activities is carried out in 2 stages. There are improving cognitive knowledge with structured education, then the next stage is skill improvement with early detection demonstrations using medical devices. Conclusion: This Upskilling and rekskilling activity for posbindu cadres can improve the knowledge and skills of NCDs posbindu cadres.